Solid waste management of tertiary hospital dietary units in Quezon City, Philippines (2010)
The study identified the practices of two tertiary hospitals' dietary units in Quezon City i terms of solid waste separation, collection/transport, storage, disposition, and administrative/training support. It also determined their prevailing activities on solid waste reduction, recycling, and reuse. Data were used to assess their compliance with existing laws and regulations. Purposive sampling was used to select the two hospitals and 11 respondents for the study. Data were gathered using survey interview, compliance checklist, and waste audit composition survey (WACS). Focus Group Discussion with selected personnel as participants was used to validate the data that were gathered. Mixed design approach was used to analyze both quantitative and qualitative data. Results revealed that both dietary units of these hospitals generated roughly 75% of biodegradable wastes in their waste stream. Pig slop comprised the largest waste at 73% and 42% in hospitals A and B, respectively. The former generated more waste despite having less patients (averaging 279 per day) compared to the latter with 459 average number of patients per day. The study showed no correlation between the number of patients and the amount of waste. The budget for food and non-food items was found to significantly (p<0.05) influence the amount of waste generated in the hospitals. Hospital A had a better compliance with Department of Health (DOH) requirements on solid waste management with an average score of 83%, while hospital B had an average score of 50%. Poor compliance was noted on the storage of solid waste for Hospital A. Hospital B exhibited poor performance in the separation and segregation of waste due to lack of supplies and materials. Lack of administrative supervision and training contributed to the observed deficiencies in the implementation of Hospital B's solid waste management program. Further studies on factors influencing compliance and waste amount generation such as food containers, attitude, food preferences of patients, and meal planning, among others is recommended.